2018
DOI: 10.1007/s12127-018-0232-4
|View full text |Cite
|
Sign up to set email alerts
|

The determination of salivary oxypurines before and after exercise by combined liquid chromatography-field asymmetric waveform ion mobility spectrometry-time-of-flight mass spectrometry

Abstract: A method combining field asymmetric waveform ion mobility spectrometry with liquid chromatography-mass spectrometry (LC-FAIMS-MS) has been developed for the analysis of the oxypurine compounds hypoxanthine (HX) and xanthine (XA) in saliva. Separation of the oxypurines from interfering matrix components was investigated using FAIMS-MS. The selected FAIMS parameters were then applied to the rapid LC-FAIMS-MS analysis of HX and XA using a short chromatographic separation method (7 min). A comparison of the LC-MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Overall, the intensity and duration of elite rugby union match play cause acute metabolite perturbations indicative of both oxidative and metabolic stress whilst fulfilling the high energy demands. The reduced salivary purine profiles due to oxidative stress have been observed post exhaustive exercise in male athletes [ 39 ]. The increase in serum 2-hydroxybutyrate post-match is indicative of the cumulative stress upon energy systems [ 40 ] and may be due to increased catabolism of l -threonine [ 41 ] and glutathione synthesis [ 42 ] in response to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the intensity and duration of elite rugby union match play cause acute metabolite perturbations indicative of both oxidative and metabolic stress whilst fulfilling the high energy demands. The reduced salivary purine profiles due to oxidative stress have been observed post exhaustive exercise in male athletes [ 39 ]. The increase in serum 2-hydroxybutyrate post-match is indicative of the cumulative stress upon energy systems [ 40 ] and may be due to increased catabolism of l -threonine [ 41 ] and glutathione synthesis [ 42 ] in response to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, exercise metabolomic studies identified more metabolites in urine relative to serum or plasma. The lowest number of metabolites identified having a significant change in any exercise metabolomic study was two as reported by Arthur et al (50) for a study looking at metabolic changes in saliva after 60 minutes of cycling ( 45minutes at an intensity of 70% of maximum power (Pmax) and greatest distance possible for a further 15 minute-period) in 11 healthy male athletes using targeted liquid chromatography flow injection analysis tandem mass/mass spectrometry (LC-FAIMS-MS).…”
Section: Metabolites and Pathways/physiological Processes Identifiedmentioning
confidence: 96%